Population Pharmacokinetic Analysis of Fluticasone Furoate/Umeclidinium/Vilanterol via a Single Inhaler in Patients with COPD. (15th May 2018) - Mehta, Rashmi; Pefani, Eleni; Beerahee, Misba; Brealey, Noushin; Barnacle, Helen; Birk, Ruby; Zhu, Chang‐Qing; Lipson, David A.
Abstract: A population pharmacokinetic analysis was conducted from a subset of samples obtained from the Lung Function and Quality of Life Assessment in Chronic Obstructive Pulmonary Disease with Closed Triple Therapy trial to characterize the pharmacokinetics of fluticasone furoate, umeclidinium, and vilanterol in patients with symptomatic COPD following treatment with fluticason furoate‐umeclidinium‐vilanterol combined in a single inhaler. This was a randomized, double‐blind, double‐dummy study comparing 24 weeks of once‐daily triple therapy (fluticason furoate‐umeclidinium‐vilanterol, 100 μg/62.5 μg/25 μg; Ellipta inhaler) with twice‐daily dual therapy (budesonide/formoterol 400 μg/12 μg; Turbuhaler). The analyses were conducted in a subset of 74 patients who received fluticason furoate‐umeclidinium‐vilanterol and provided serial or sparse samples. Monte Carlo simulations and a model‐based estimation approach both indicated that systemic drug concentrations of fluticasone furoate, umeclidinium, and vilanterol after administration of fluticason furoate‐umeclidinium‐vilanterol triple combination therapy from a single inhaler were within the ranges observed following administration of these drugs as monotherapy (fluticasone furoate, umeclidinium, and vilanterol) or as dual‐combination therapy (fluticasone furoate/vilanterol or umeclidinium/vilanterol).